Warmth and competence perceptions of key protagonists are associated with containment measures during the COVID-19 pandemic: Evidence from 35 countries (vol 12, 21277, 2022) - Friehs, Maria-Therese; Kotzur, Patrick F.; Kraus, Christine; Schemmerling, Moritz; Herzig, Jessica A.; Stanciu, Adrian; Yzerbyt, Vincent (Nature Portfolio, 2023)
[Abstract Not Available]